No exit : what parents owe their children and what society owes parents - Alstott, Anne, 1963- (OUP E-Books., 2004)
In order to create a more secure world for children and their parents, Anne Alstott argues, we must fundamentally change the way we think about parents' obligations to children - and about society's obligations to parents. She proposes a solution both pragmatic and controversial.